A clinical study into the impact of brief aerobic exercise on the cardiopulmonary function of patients diagnosed with hyperlipidemia - Zhang, Hua; Ge, Ya-Ru; Feng, Li; Zhang, Jing; Wang, Ning; Zhang, Xiao-Yan; Liu, Cong (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe aim of this study was to examine the effectiveness of brief aerobic exercise on patients diagnosed with hyperlipidemia.MethodsSeventy patients diagnosed with hyperlipidemia were enrolled from community health centers between May 2023 and October 2023. They were randomly assigned into two groups: test and control group, each consisting of 35 patients. The test group received personalized exercise recommendations along with routine medication, while the control group only received routine medication. The effectiveness of the intervention was assessed after 3 months. Various indicators including blood pressure, lipid levels, changes in cardiopulmonary function, 6-minute walk distance (6MWD) test results, the percentage of 6MWD relative to the predicted value (6MWD%Pred), copeptin (CPP), and fibroblast growth factor 21 (FGF21) were compared, before and after the intervention within each group and between the two groups.ResultsAfter 3 months of personalized exercise, the test group showed significantly higher levels in three indicators compared to the control group. Specifically, the test group exhibited higher metabolic equivalent (MET) values [(x¯ ± SD, 4.6 ± 0.27 METs) vs. (x¯ ± SD, 3.8 ± 1.06 METs); P < 0.05], longer 6-minute walk distance (6MWD) [(x¯ ± SD, 488.08 ± 40.59 meters) vs. (x¯ ± SD, 366.76 ± 160.49 meters); P < 0.05], and a higher percentage of 6MWD relative to the predicted value (6MWD %Pred) [(x¯ ± SD, 92.8 ± 14.05) vs. (x¯ ± SD, 71.3 ± 30.69); P < 0.05]. Additionally, within the test group, there was a significant increase in MET, 6MWD, and 6MWD%Pred compared to baseline (P < 0.05).ConclusionShort-term aerobic exercise shows significant improvement in the cardiopulmonary function of patients with hyperlipidemia. However, it did not exhibit significant efficacy in managing hyperlipidemia.